2005
DOI: 10.1002/esp.1224
|View full text |Cite
|
Sign up to set email alerts
|

Till deposition by glacier submarginal, incremental thickening

Abstract: Macro-and micro-scale sedimentological analyses of recently deposited tills and complex push/squeeze moraines on the forelands of Icelandic glaciers and in a stacked till sequence at the former Younger Dryas margin of the Loch Lomond glacier lobe in Scotland are used to assess the depositional processes involved in glacier submarginal emplacement of sediment. Where subglacial meltwater is unable to flush out subglacial sediment or construct thick debris-rich basal ice by cumulative freeze-on processes, glacier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
190
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(205 citation statements)
references
References 70 publications
12
190
2
1
Order By: Relevance
“…Evans & Hiemstra 2005). Macrofabric measurements of the dip and azimuth 72 (orientation) of the A-axis and A/B plane of clasts were taken using a compass clinometer, aiming to use 73 predominantly clasts in the range of 30-125 mm (A-axis length) to allow comparison with other studies 74 (Benn 1994a al.…”
Section: Methods 62mentioning
confidence: 99%
See 1 more Smart Citation
“…Evans & Hiemstra 2005). Macrofabric measurements of the dip and azimuth 72 (orientation) of the A-axis and A/B plane of clasts were taken using a compass clinometer, aiming to use 73 predominantly clasts in the range of 30-125 mm (A-axis length) to allow comparison with other studies 74 (Benn 1994a al.…”
Section: Methods 62mentioning
confidence: 99%
“…This further enabled Benn 42 (1995) to assign clast macrofabric signatures as well as textural characteristics to the different styles of 43 subglacial sediment deformation. Similarly, Evans and Hiemstra (2005) reported sedimentological and 44 clast macrofabric data collected from sub-marginal till wedges that had been stacked to produce a 45 complex push moraine during a period of glacier readvance in southern Iceland during the 1990s. Both 46 studies have proposed potentially diagnostic sedimentological criteria for the identification of subglacial 47 processes such as brittle and ductile deformation and lodgement.…”
mentioning
confidence: 96%
“…Localized exposures through the push ridges reveal deformed stratified sediments indicative of recent glacier readvance into proglacial outwash, potentially driven by the mid to late 1990s positive mass balance trends recognized throughout Iceland (e.g. Bennett & Evans, 2012;Bradwell, Dugmore, & Sugden, 2006;Evans & Hiemstra, 2005;Evans, Shand, & Petrie, 2009, 2015b.…”
Section: Till and Morainesmentioning
confidence: 99%
“…This is because of the critical role subglacial meltwater plays in regulating the dynamics of ice masses, ice-marginal behaviour and associated hydrogeological systems within subglacial, marginal and proglacial areas (Boulton & Hindmarsh, 1987;Piotrowski et al, 2004Piotrowski et al, , 2006Evans & Hiemstra, 2005;Evans et al, 2006;Robinson et al, 2007;Boulton et al, 2009;Bartholomew et al, 2010). Put simply, subglacial meltwater deposits are the product of a hydrological regime that is not unique to subglacial environments, with similar regimes documented from a range of other sedimentary environments including intertidal (Cheel & Middleton, 1986), fluvial (Cheel, 1990, Røe, 1987Alexander et al, 2001) and channelised turbidity currents (Ito & Saito, 2006).…”
Section: 3mentioning
confidence: 99%
“…Changes are driven by standard processes that control groundwater systems, plus processes that operate within glacial environments including seasonal variations in temperature and meltwater flux, glacier surges and outburst floods (Robinson et al, 2007). Several studies have demonstrated that such groundwater variability can exert a significant influence on subglacial and ice-marginal processes (Sharp, 1984;Krüger, 1994;Evans & Hiemstra, 2005) and this could have facilitated -at least locally, an ice-marginal readvance and deposition of the upper diamicton. This diamicton has been attributed elsewhere around the Irish Sea Basin with enhanced rates of basal sliding associated with the Late Weichselian Irish Sea Ice Stream (Ó Cofaigh & Evans, 2001a,b;Phillips et al, 2010).…”
Section: 4mentioning
confidence: 99%